Simulation of directed energy deposition powder nozzle flow to investigate powder flow and density - Dinny Afiq Razali (Nanyang Technological University, 2020)
The aim of this Final year Project was to investigate the effects of Powder Mass Flow rate and Carrier Gas flow rate on Powder Deposition in the Direct Energy Deposition additive manufacturing process. Efficient utilisation of feedstock powder is important in this field in order for the manufacturing process to become a sustainable one. Computer simulations of the powder deposition process were carried out using ANSYS Fluent with varying powder and carrier gas flow rates to observe their effects on the deposition of the powder. Powder was simulated to be blown from inside a powder nozzle and into a control volume which would be used to measure the mass and concentration of powder particles entering. The results obtained showed that raising both powder mass flow rate and carrier gas flow rate caused an increase in the amount of powder blown from the nozzle. This indicated that both powder mass flow rate and carrier gas flow rate had a significant effect on the amount of powder delivered by the powder nozzle. Higher carrier gas flow rates were additionally noted to cause a more pointed or cone shaped dispersion of particles emanating from the powder nozzle. This indicated that carrier gas flow rates could have an effect upon the concentration of powder that is blown towards the target deposition point on the substrate, particularly for higher gas flow rates.